Chemical and nutritional characteristics, and microbial degradation of rapeseed meal recalcitrant carbohydrates: A review - Long, Cheng; Qi, Xiao-Long; Venema, Koen (Frontiers in Nutrition, 2022)
Approximately 35% of rapeseed meal (RSM) dry matter (DM) are carbohydrates, half of which are water-soluble carbohydrates. The cell wall of rapeseed meal contains arabinan, galactomannan, homogalacturonan, rhamnogalacturonan I, type II arabinogalactan, glucuronoxylan, XXGG-type and XXXG-type xyloglucan, and cellulose. Glycoside hydrolases including in the degradation of RSM carbohydrates are α-L-Arabinofuranosidases (EC 3.2.1.55), endo-α-1,5-L-arabinanases (EC 3.2.1.99), Endo-1,4-β-mannanase (EC 3.2.1.78), β-mannosidase (EC 3.2.1.25), α-galactosidase (EC 3.2.1.22), reducing-end-disaccharide-lyase (pectate disaccharide-lyase) (EC 4.2.2.9), (1→4)-6-O-methyl-α-D-galacturonan lyase (pectin lyase) (EC 4.2.2.10), (1→4)-α-D-galacturonan reducing-end-trisaccharide-lyase (pectate trisaccharide-lyase) (EC 4.2.2.22), α-1,4-D-galacturonan lyase (pectate lyase) (EC 4.2.2.2), (1→4)-α-D-galacturonan glycanohydrolase (endo-polygalacturonase) (EC 3.2.1.15), Rhamnogalacturonan hydrolase, Rhamnogalacturonan lyase(EC 4.2.2.23), Exo-β-1,3-galactanase (EC 3.2.1.145), endo-β-1,6-galactanase (EC 3.2.1.164), Endo-β-1,4-glucanase (EC 3.2.1.4), α-xylosidase (EC 3.2.1.177), β-glucosidase (EC 3.2.1.21) endo-β-1,4-glucanase (EC 3.2.1.4), exo-β-1,4-glucanase (EC 3.2.1.91), and β-glucosidase (EC 3.2.1.21).This review summarizes the chemical and nutritional compositions of RSM, and the microbial degradation of RSM cell wall carbohydrates which are important to allow to develop strategies to improve recalcitrant RSM carbohydrate degradation by the gut microbiota, and eventually to improve animal feed digestibility, feed efficiency, and animal performance.